Developmental Diseases of the Hip Diagnosis and Management - Spasovski, Dusko (IntechOpen, 2017)
There is a long list of diseases and traumatic events that affect hip joint, but none as persistent, as elusive and with profound consequences as developmental dysplasia. For many centuries, we have been struggling with its consequences while trying to understand the reasons how and why such a stable joint eventually becomes dysfunctional and how to prevent it. Some of the greatest achievements in operative orthopaedics have been introduced in the effort to treat developmental dysplasia of the hip. This book offers a contemporary approach to developmental dysplasia of the hip, covering various clinically relevant aspects - historical and epidemiological considerations, biomechanical analysis, conservative methods and operative treatment procedures.